Exploring Aggressiveness and Disclosure of Tax: A Bibliometric Analysis Approach - Sari Mujiani; Rudi Zulfikar; Helmi Yazid; Ina Indriana (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to conduct a bibliometric analysis of the literature on tax aggressiveness and tax disclosure, including research trends, main themes, intellectual structure, and future research opportunities in accounting and taxation. Method: This study conducts a bibliometric analysis to review the literature on tax aggressiveness and disclosure systematically. A bibliometric analysis was conducted to examine the patterns, trends, and intellectual structure of the literature on tax aggressiveness and disclosure. Results: The analysis spans from 1991 to 2024, encompassing 998 papers and 73,816 citations. Key findings reveal influential works, thematic clusters, author collaborations, and emerging research trends. Thematic clusterization identifies four distinct areas: international financial reporting, taxation strategies, corporate social responsibility, and empirical analyses of corporate governance. Temporal trend analysis highlights a shift towards broader corporate governance concerns, particularly social responsibility and gender diversity. Author collaboration networks reveal relationships among authors and isolated authors within the research community. Novelty: This research integrates bibliometric mapping of tax aggressiveness and tax disclosure to identify trends and themes.